(3af EOGQI GdJfGaSs - (3cQjSJhaQ(B, (3ejQajs; (3NGdO GdYGeQj(B, s ((3GdbGgQI(B;(3eDSSI eMeO Hf QGTO Bd ecJhe(B:s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B,s, 2008)
(3jVe cjajI RjGOI GdaGYdjI aj EOGQI GdJfGaS, YOe GdEcJaGA HeQGbHI GdefGaSjf, GdJWHjb GdYedj daf EOGQI GdJfGaS, GdJfGaS Hjf GdTQcGJ, GdYhGed GdOGNdjI GdCSGSjI dfeh GdTQcGJ, GdYhGed GdNGQLjI GdCSGSjI dfeh GdTQcI, GdfhGMj GdbGfhfjI hGdCNdGbjI aj af EOGQI GdJfGaS, eQMdI LeY GdHjGfGJ, GdJNWjW hLeY GdHjGfGJ GdChdjI, GdHjFI GdJfGaSjI, JfbjM GdHMK, JbOje GdeSJfOGJ GdQSejI GdOhQjI, GdeUGOQ GdCLfHjI, GSJNdGU GdeYdheGJ ef NdGd GddbGAGJ GdTNUjI, JMhjd GdHjGfGJ GdChdjI Edi eYdheGJ fgGFjI, GdebGQfI Hjf GdTQcGJ hJMOjO eQGWRgG, GdhbGjI ef CfTWI EOGQI GdJfGaSs
(3cTGa eUWdMGJ U(B.429s
Keywords: (3GdESJQGJjLjI GdJfGaSjIs; (3GdefGaSIs